Building Sustainable Cities through the Integration of Vernacular Architecture - Viana, Kelly Mares (Technical and Scientific Journal Green Cities, 2024)
This article explores the integration of vernacular architecture and sustainable practices in contemporary urban planning as an innovative approach to building more sustainable cities. Beginning with an analysis of the importance of vernacular architecture as an expression of local culture and traditional knowledge, the article highlights how these practices can be adapted and incorporated into modern urban projects. By examining the tangible and intangible benefits of this approach, including the reduction of environmental impact, preservation of cultural identity, and strengthening of community, the article demonstrates the significant potential of integrating vernacular architecture in creating more livable and resilient cities. Through case studies and practical examples, the article illustrates how the combination of traditional building techniques with contemporary innovations can lead to positive outcomes in terms of energy efficiency, use of sustainable materials, and urban quality of life. Ultimately, the article emphasizes the importance of recognizing and valuing cultural and environmental diversity in our urban development process, highlighting vernacular architecture as a rich source of inspiration and solutions for the cities of the future.
Keywords: Sustainability; Vernacular Architecture; Urban Planning